A Review on the Carcinogenic Roles of DSCAM-AS1 - Ghafouri-Fard, Soudeh; Khoshbakht, Tayyebeh; Taheri, Mohammad; Ebrahimzadeh, Kaveh (Frontiers in Cell and Developmental Biology, 2021)
Long non-coding RNAs (lncRNAs) are a group of transcripts with fundamental roles in the carcinogenesis. DSCAM Antisense RNA 1 (DSCAM‐AS1) is an example of this group of transcripts which has been firstly identified in an attempt to find differentially expressed transcripts between breast tumor cells and benign breast samples. The pathogenic roles of DSCAM-AS1 have been vastly assessed in breast cancer, yet its roles are not restricted to this type of cancer. Independent studies in non-small cell lung cancer, colorectal cancer, osteosarcoma, hepatocellular carcinoma, melanoma and cervical cancer have validated participation of DSCAM-AS1 in the carcinogenic processes. miR-577, miR-122-5p, miR-204-5p, miR-136, miR‐137, miR‐382, miR‐183, miR‐99, miR-3173-5p, miR-874-3p, miR-874-3p, miR-150-5p, miR-2467-3p, miR-216b, miR-384, miR-186-5p, miR-338-3p, miR-877-5p and miR-101 are among miRNAs which interact with DSCAM-AS1. Moreover, this lncRNA has interactions with Wnt/β-catenin pathway. The current study aims at summarization of the results of studies which focused on the assessment of oncogenic role of DSCAM-AS1.